Preparation of preschool child psychology and modern methods used in it - Ismailova Sabina Erkin qizi (International Journal on Orange Technologies, 2021)
This article describes in detail the quality of preparation of preschool children for school, as well as information about child psychology and innovative psychological methods that develop their potential.